2002
DOI: 10.1159/000068018
|View full text |Cite
|
Sign up to set email alerts
|

The Stanley Foundation Bipolar Network: Results of the Naturalistic Follow-Up Study after 2.5 Years of Follow-Up in the German Centres

Abstract: The Stanley Foundation Bipolar Network (SFBN) is an international, multisite network investigating the characteristics and course of bipolar disorder. Methods (history, ratings and longitudinal follow-up) are standardized and equally applied in all 7 centres. This article describes demographics and illness characteristics of the first 152 German patients enrolled in the SFBN as well as the results of 2.5 years of follow-up. Patients in Germany were usually enrolled after hospitalisation. More than 72% of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 14 publications
1
31
0
5
Order By: Relevance
“…These findings are consistent with reports from the Stanley Foundation Bipolar German cohort, in which 40% of "rapid cyclers" suffered a recurrent rapidcycling course during a 2.5-year follow-up period. 9 A Veterans Affairs study cohort found that 14% of bipolar patients had experienced rapid cycling in the 12 months prior to intake (and 33% during the follow-up period), 10 while Schneck and colleagues 11 report a rapid-cycling rate of 20% in their cohort of 500 bipolar patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with reports from the Stanley Foundation Bipolar German cohort, in which 40% of "rapid cyclers" suffered a recurrent rapidcycling course during a 2.5-year follow-up period. 9 A Veterans Affairs study cohort found that 14% of bipolar patients had experienced rapid cycling in the 12 months prior to intake (and 33% during the follow-up period), 10 while Schneck and colleagues 11 report a rapid-cycling rate of 20% in their cohort of 500 bipolar patients.…”
Section: Discussionmentioning
confidence: 99%
“…The reported risk of mood episodes, however, does vary considerably between long-term randomized controlled trials (RCT) and prospective, naturalistic studies. Within naturalistic trials, a considerable variance in the rates of and delay to new mood episodes was observed [5,6,7,8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…This is partially responsible for the varying prevalence rates among studies and the confl icting opinions between authors. Any anxiety disorder is reported to be present in 42-93 % of patients during lifetime and in almost 11-70 % cross-sectionally (Young et al 2013 ;Tamam and Ozpoyraz 2002 ;Altshuler et al 2010 ;Zutshi et al 2006 ;Simon et al 2004b ;Kawa et al 2005 ;Kessler et al 1997 ;Levander et al 2007 ;Nakagawa et al 2008 ;Goldstein and Levitt 2008 ;Schaffer et al 2006 ;Otto et al 2006 ;Nery-Fernandes et al 2009 ;Mantere et al 2006Mantere et al , 2010Henry et al 2003 ;Freeman et al 2002 ;Dittmann et al 2002 ;Das 2013 ;Cosoff and Hafner 1998 ;Ciapparelli et al 2007 ;Bellani et al 2012 ;McElroy et al 2001 ;Boylan et al 2004 ;Szadoczky et al 1998 ;Weber et al 2011 ;Azorin et al 2009 ). Up to half of these BD patients with comorbid anxiety manifest at least two anxiety disorders (Henry et al 2003 ).…”
Section: Comorbid Anxietymentioning
confidence: 99%
“…The relationship of comorbid anxiety with suicidality is questionable (Slama et al 2004 ). Probably it is more frequent in BD-II than in BD-I patients (Dittmann et al 2002 ), although rapid cycling and substance abuse might reverse this and dramatically increase anxiety rates in BD-I (Gao et al 2008 ).…”
Section: Comorbid Anxietymentioning
confidence: 99%
See 1 more Smart Citation